LEARNING QUALITY MANAGEMENT AT SMP DARUL ARQAM GOMBARA MAKASSAR - Martini, Martini; Mus, Abdul Rahman; Hakim, Ahmad; Syahid, Akhmad (Jurnal Diskursus Islam, 2021)
This study examined in depth the management of learning quality by looking at the four management components, namely Planning, Organizing, Actuating, and Controlling (POAC) at SMP Darul Arqam Gombara Makassar. The research uses a qualitative phenomenological approach, with the type of research being a multi-site study. Data collection techniques through questionnaires, interviews, observation and documentation. The data were analyzed using an interactive analysis model consisting of data collection, data reduction, data presentation, verification, and conclusions. This study indicates that learning quality management at SMP Darul Arqam Makassar is implemented through four steps. First, learning planning according to Process Standards with innovative and accelerated curriculum content with the demands of the current education "market" and designed in an integrated manner between academic and non-academic activities based on progress and superiority. Second, learning organizations with well-placed resources integrated academic and non-academic schedules and internal institutional support for human resource development. Third; implementation of learning supported by competent and professional educators; adequate learning media; innovation in facilitating active, creative, fun learning; and an objective and accountable scoring system. Fourth, learning supervision by an objective and transparent performance appraisal system, internal and external supervisors with integrity.